PELATIHAN PEMBUATAN SOAL DAN PENILAIAN DARING BAGI GURU SMP N 1 KEDIRI (LPPM Universitas PGRI Mahadewa Indonesia, 2021)
As an educator, the teacher is obligated to enhance the consistency of the learning process, which has a direct effect on their students' abilities. As a result, teachers are expected to maintain their competencies, one of which is professional competence. This community service activity (PKM) aims to add insight and improve the competence of junior high school teachers, through training in question developing and online assessment. The new period of digitalization has seen an explosion in the use of information technology (IT) across multiple sectors/fields, including education. Educational institutions are required to be able to use computer technology to carry out all aspects of the learning process, from instruction to evaluation. Particularly during the pandemic conditions, it is required to introduce the online learning and evaluation method. This PKM operation involves three stages: preparation, implementation, and evaluation. This PKM activity makes use of teaching, mentoring, and discussion. The training is conducted by presenting information on how to develop questions and administer online tests. The material presented includes policies for implementing online assessments before and during the pandemic as well as making online questions and assessments using the google form. The outcomes of this PKM activity include the following: 1) increased teacher awareness and comprehension of the use of Google Forms as a tool for conducting online assessments; and 2) increased teacher enthusiasm for improving pedagogic competence. Additionally, the results of this PKM indicate a high level of satisfaction among trainee teachers, with a very satisfied percentage of 82% and a satisfied percentage of 18%